The Effect of The Project-Based Learning Model on High School Students' Science Process Skills - Rizka Sofia Irawan; Samsul Sahidi; Rifdah Fadhilah; Ridha Zulfatun Nafisah; Khaerul Anam (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Project-Based Learning is an instructional strategy that improves students' Science Process Skills (SPS) by involving them in hands-on scientific project design and implementation. This study investigates the effect of PjBL on students’ SPS, focusing on skills such as observing, generating hypotheses, planning experiments, using tools and materials, collaborating in groups, and communicating scientifically. The research follows a quasi-experimental design with a pretest-posttest control group, including two XI classes at SMAN 1 Lembar, selected through purposive sampling. One class (XI-1) is assigned to the experimental group, which uses PjBL, while the other (XI-2) is the control group, which follows traditional teaching methods. The study uses a science process skills test as the research instrument. The N-Gain analysis showed a moderate improvement of 0.335 in the experimental group, compared to a minimal improvement of 0.011 in the control group. A t-test (t = 6.84 > t = 1.673 at the 5% significance level) confirmed the significant effect of PjBL. The results indicate that PjBL effectively enhances students’ scientific skills, critical thinking, and creativity, making it a viable and innovative approach for science education. These results suggest that PjBL can be foundational to developing more integrated, context-driven approaches to science learning.